Egg Production and Quality of IPB D3 Chicken and It’s Repeatability Estimation - M. F. Hawari; C. Sumantri; S. Darwati (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
High egg production and good egg quality for IPB D3 chicken is very important to produce a lot and quality DOC, then a high repeatability value is also needed to maintain continuous DOC availability. The purpose of this study was to examine the estimated repeatability value of egg production and eggquality as well as the production performance and quality of chicken eggs IPB D3. The observed poultry were 30 IPB D3 G3 females and 90 eggs. Repeatability values were analyzed using a variance table and egg production and quality data were analyzed descriptively. The repeatability value of egg production is 0.42 (high), the Haugh unit repeatability of egg is 0.40 (medium), the egg weight repeatability value 0.67 (high), the egg yolk score repeatability value 0.40 (medium) and the egg index repeatability value 0.95 (high). Egg weight 40.76 g, Haugh unit value 76, and egg production 44.8%.